2022
DOI: 10.1155/2022/7844524
|View full text |Cite
|
Sign up to set email alerts
|

An Entropy Weight‐TOPSIS Based Model for Partner Selection of Strategic Alliance of Prefabricated Construction Enterprises

Abstract: Selecting the right partner is a key factor for the successful construction of the strategic alliance of prefabricated construction enterprises in China. Based on the summarization of domestic and foreign studies, combined with the characteristics of the strategic alliance of prefabricated construction enterprises, the paper has constructed an evaluation indicator system of the partner selection of the strategic alliance of prefabricated construction enterprises in China. The paper also has conducted an empiri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…However, it has an impact on the optimization of the revenue allocation ratio. Guo et al (2022) constructed a strategic alliance partner selection evaluation model based on entropy weight and technique for order of preference by similarity to ideal solution (TOPSIS) for assembled buildings. They concluded that commercial property sales capability, property management capability, capital investment, talent investment, and product innovation capability are the five most influential secondary indicators.…”
mentioning
confidence: 99%
“…However, it has an impact on the optimization of the revenue allocation ratio. Guo et al (2022) constructed a strategic alliance partner selection evaluation model based on entropy weight and technique for order of preference by similarity to ideal solution (TOPSIS) for assembled buildings. They concluded that commercial property sales capability, property management capability, capital investment, talent investment, and product innovation capability are the five most influential secondary indicators.…”
mentioning
confidence: 99%